Optical, structure, and surface properties of ternary In xGa1-xN (x = 0.39–0.58) film coatings for optoelectronics: in the perspective of sputter pressure - Asım, Mantarcı (Springer Science and Business Media Deutschland GmbH, 2021)
Optical, structure, and surface properties of ternary InxGa1-xN film coatings produced under various sputtering pressures (6, 7, 8, 9, and 10 mTorr) were investigated. The crystalline size of the films increased as a general trend, except for the case from 6 to 7 mTorr and from 9 to 10 mTorr. The indium ratio in the InGaN thin film was calculated using Vegard Law as x = 0.39, 0.58, 0.55, 0.40 at changes sputtering pressures. Ga–N, N–O, In2O3, InNxOy bonding of thin film was obtained, from XPS analysis. Optical band gap energies of films were varied, mainly originated from different Indium ratios at different pressures. Varying sputter pressures has greatly altered the optical conductivity of the film. Thornton model has been valid for surface properties of our films and has complied with our results. In essence, our analysis in different sputter pressure perspectives will be able to shed light on future InGaN-based studies. © 2021, King Abdulaziz City for Science and Technology.
Keywords: Coatings; Experimental methods; Indium ratio; Optical conductivity; Sputter pressure; Thornton model